Impoliteness strategies in the social media comments on the Low Yat plaza incident / Jane Xavierine M Xavier Thayalan - Jane Xavierine , M Xavier Thayalan (2017)
The study investigates impoliteness strategies and the realization of language used by YouTube interlocutors when discussing the Low Yat Plaza incident. On the wake of the brawl at Low Yat Plaza, which shook the nation on 12th July 2015, many Malaysians took to social media such as YouTube to express their thoughts on the issue. A small theft incident at the plaza had become a racial frenzy over social media and therefore, it is puzzling how the incident can occur when politeness and respect are the central belief of the Malaysian society. Besides, the study aims to analyse impoliteness strategies used by Malaysians in social media comments that causes social face damage and analyse impoliteness in the language used by Malaysians. The data were drawn from two videos posted in YouTube.com which depicts impolite interactions between interlocutors. Both videos were chosen because it had the most number of impolite comments by YouTube users. Culpeper’s (2011) Impoliteness Framework was used to qualitatively analyse 123 comments gathered. Findings of the study show that Malaysians used the strategy of ‘insult’ most frequently as a form of impolite talk in their respective comments and profanities were the most used linguistic device to cause social face damage to interlocutors. Apart from those strategies propagated by Culpeper (2011), other new categories of insult emerge which illustrates that Culpeper (2011) Impoliteness framework cannot be replicated completely in an Asian setting. The new categories of insult include accusation and baseless claims, show of superiority as well as mock and ridicule.